Reactive oxygen species induce virus-independent MAVS oligomerization in systemic lupus erythematosus - Buskiewicz, Iwona A; Montgomery, Theresa; Yasewicz, Elizabeth C; Huber, Sally A; Murphy, Michael P; Hartley, Richard C; Kelly, Ryan; Crow, Mary K; Perl, Andras; Budd, Ralph C; Koenig, Andreas (Science signaling, 2016)
The increased expression of genes induced by type I interferon (IFN) is characteristic of viral infections and systemic lupus erythematosus (SLE). We showed that mitochondrial antiviral signaling (MAVS) protein, which normally forms a complex with retinoic acid gene I (RIG-I)-like helicases during viral infection, was activated by oxidative stress independently of RIG-I helicases. We found that chemically generated oxidative stress stimulated the formation of MAVS oligomers, which led to mitochondrial hyperpolarization and decreased adenosine triphosphate production and spare respiratory capacity, responses that were not observed in similarly treated cells lacking MAVS. Peripheral blood lymphocytes of SLE patients also showed spontaneous MAVS oligomerization that correlated with the increased secretion of type I IFN and mitochondrial oxidative stress. Furthermore, inhibition of mitochondrial reactive oxygen species (ROS) by the mitochondria-targeted antioxidant MitoQ prevented MAVS oligomerization and type I IFN production. ROS-dependent MAVS oligomerization and type I IFN production were reduced in cells expressing the MAVS-C79F variant, which occurs in 30% of sub-Saharan Africans and is linked with reduced type I IFN secretion and milder disease in SLE patients. Patients expressing the MAVS-C79F variant also had reduced amounts of oligomerized MAVS in their plasma compared to healthy controls. Together, our findings suggest that oxidative stress-induced MAVS oligomerization in SLE patients may contribute to the type I IFN signature that is characteristic of this syndrome.